Molecular characterization of aeromonas hydrophila isolated from pangasius hypophthalmus (sauvage, 1878) in Pahang river, Malaysia - Mansor, Nur Nazifah; Abdullah, Siti Zahrah; Mohamad, Syamil; Sulaiman, Sofiyah Amiera (2016)
Pahang, Malaysia are very famous of its Pangasius spp (Patin) aquaculture activity. Pangasius spp. has excellent potential for inland aquaculture system with its fast growing ability and good market value in European markets (Singh and Lakra, 2012).Pangasius spp. is one of the largest and most important inland fisheries in the world which mainly contribute as a food source. The production of Pangasius spp. in Malaysia showed tenfold increased from 1,625.21 tonnes in 2000 to 10,891.51 tonnes in 2011. However, Pangasius culture has been reported to face disease problem causing almost 30% mortalities especially in Sungai Pahang and Sungai Kuantan due to multiple infections of bacteria and virus. The reported bacterial disease was Motile Aeromonas Septicemia (MAS) while virus is channel catfish virus (CCV). Thus, the aim of this study is to understand Aeromonas hydrophila that had cause MAS infection in Pangasius hypophthalmus at Pahang River.